Species of coagulase-negative staphylococci isolated from catheter tips from open-heart surgery patients. Issue 5 (May 1980) - Freeman, R; Hjersing, N
Abstract : Coagulase-negative staphylococci isolated from the tips of catheters used in open-heart surgical patients were classified into species and the results compared with those obtained by speciation of coagulase-negative staphylococci isolated as blood culture contaminants. Staphylococcus epidermidis was the most common species in both populations, but other species occurred more often in the catheter tip group. Staphylococcus saprophyticus was found in 17% of the catheter tip series and was not found at all in the blood cultured contaminants. Species other than S epidermidis, and particularly S saprophyticus, were isolated more often from catheters which had been in situ some days. These findings suggest that speciation of coagulase-negative staphylococci from catheter tips may point to some species being better adapted to colonise and survive on prosthetic materials. In this study such evidence suggested that S saprophyticus might be such a species. It is concluded that if the initial results presented here are confirmed, a more logical approach to the chemoprophylaxis of prosthetic implant surgery would be possible.